Empowering access: unveiling an overall composite spatial accessibility index to healthcare services in Southeastern Iran - Ahmad Raeesi; Soheil Hashtarkhani; Mahmood Tara; Narjes Sargolzaei; Behzad Kiani (International Journal for Equity in Health)
Abstract Background Access to healthcare is critical for population health; however, geographic barriers persist especially in rural and deprived regions. This study aims to develop an overall composite potential spatial accessibility index to healthcare facilities and services in Sistan and Baluchestan Province in southeast Iran. Methods This study employed the enhanced two-step floating catchment area (E2SFCA) method to create an overall composite spatial accessibility index for healthcare facilities and services in Sistan and Baluchestan Province, southeast Iran. Spatial accessibility for general practitioners, nursing, dentistry, midwifery, pharmacy, medical laboratory, nutrition, public health, radiology, psychology, environmental health, rural health workers, inpatient hospital beds, and five medical specialty services were calculated. Spatial accessibility scores were normalized from 0 to 1 (no access = 0, low = 0.01 to 0.33, moderate = 0.331 to 0.66, high = 0.661 to 1) and aggregated into overall indices of primary, secondary, and overall healthcare accessibility for each district. Inequality was assessed using the Lorenz curve and Gini coefficient analysis. Results Low geographic accessibility was found across Sistan and Baluchestan Province, especially in rural areas. Almost 75% of the population had low/no access to overall primary care services within a 30-minute drive time. For secondary care, nearly 45% had low/no access to hospital inpatient beds within a 30-minute drive time, and around 40% had low/no access to specialists within a 60-minute drive time. Just 11.6% of the population had high overall healthcare access. The calculated Gini coefficient of 0.517 for the overall spatial accessibility index to healthcare services in Sistan and Baluchestan Province highlights a highly unequal distribution of healthcare services. Conclusions This study demonstrates a useful replicable methodology that combines individual service accessibility metrics into an overall spatial healthcare access index. Furthermore, this study provides evidence of major shortfalls in healthcare access across Sistan and Baluchestan Province. Targeted strategies are required to increase the availability and capacity of services in underserved communities. Improving geographic access is key for progressing towards universal coverage and better population health.